The Relationship between Leg Explosive Power and Eye-Hand Coordination with Smash Skills of Volleyball Athletes - A Nurmutmainnah; Muhammad Faisal Lutfi Amri (Journal of Innovative and Creativity, 2025)
Smash is the main attack technique in volleyball which requires physical strength, precision and good coordination. This study aims to analyze the influence of explosive leg power and eye-hand coordination on smash skills in volleyball games among student volleyball athletes. The research uses quantitative methods with a correlational approach. The research sample consisted of a number of volleyball athletes who were selected purposively. Data collection instruments include a vertical jump test to measure explosive leg power, a tennis ball throw-catch test to measure hand-eye coordination, and a smash skill test in volleyball. The results of the analysis show that leg explosive power has a significant effect on smash skills. Apart from that, eye-hand coordination also makes a significant contribution. Simultaneously, these two variables are proven to have a strong influence on smash skills in volleyball. These findings emphasize that the development of physical condition and coordinative skills needs to be integrated in training programs. Thus, coaches are advised to design volleyball training that integrates increasing leg explosive power with hand-eye coordination training to optimize athletes' smash skills. Based on the results of the research and discussion that has been carried out, it can be concluded that both leg explosive power and eye-hand coordination have a significant influence on volleyball smash skills in student athletes.